Significance of effluent dose in continuous renal replacement therapy in children - Satheesh Ponnarmeni; Sasidaran Kandasamy; J. Shobana (Wolters Kluwer Medknow Publications, 2024)
Continuous renal replacement therapy (CRRT) is one of the commonly used extracorporeal blood purification therapies and its use in the pediatric population has increased in the past two decades due to the availability of safer machines which allow lower blood flow rate and dialysate flow rate. The usual indication for initiation of CRRT is for solute clearance and or fluid removal in oliguric patients with acute kidney injury. Knowledge regarding the principles of solute removal and fluid removal along with the application of these mechanisms in different modes of CRRT helps the physician to decide on the appropriate therapy for the given patient. Understanding the concept of CRRT dose and the factors to be considered in the prescription for achieving the preset targets of CRRT is vital for the efficient utilization of the therapy.